Integration of User Centered Game Design (UCGD) into game design framework - Ahmad, Ibrahim; Jaafar, Azizah (Trans Tech Publications, 2013)
Generally, computer game is a game that visualized through a media which requires interaction from players by using devices. A good feature of computer game includes high level of interactivity as well as attractive design will give freedom to players playing in the world of fantasy which it produced while playing. There are several model designs that can be used as frameworks in producing the game. However User Centered Games Design (UCGD) is one of the main references when designing a computer game. In this working paper, we discusses relevant models that certainly used by computer game designer to produce a game that will be enjoyed by users